Synthesis of MgO Using the Sol-gel Method: Correlation Between CTAB Surfactant Concentration and MgO Properties - Silva, Gabriel R. [UNESP]; Assis, Matheus S. [UNESP]; de Souza, João C.P. [UNESP]; Possato, Luiz G. [UNESP] (FapUNIFESP (SciELO), 2024)
In this work, the surfactant cetyltrimethylammonium bromide (CTAB) was applied to observe how increasing the surfactant’s concentration will affect the MgO characteristics, such as the increase in vacancies. The samples were characterized by X-ray diffraction (XRD). For the MgO-0.025CTAB sample, the intensity of the (200) peak of MgO decreased by three. However, the MgO-2.5CTAB showed an increase in the peaks intensity. In addition to using Rietveld refinement, it is possible to observe the textural characteristics of the samples, with the introduction of CTAB, oxygen vacancies increased, and from the MgO to the MgO-0.025CTAB sample, there was a decrease in oxygen occupancy from 94% to 82% in the unit cell. Thermogravimetry (TG) analyses were used to understand the interactions between the support and the surfactant as the CTAB concentration increased. With the physisorption of N2, the behavior of the sample pores and specific area determination are verified. The introduction of CTAB caused the decrease of the specific area from 32 m2/g to 9 m2/g for the MgO and MgO-0.025CTAB samples. However, for a more concentrated surfactant, MgO-2.5CTAB, the specific area was 25 m2/g. Scanning electron microscopy made it possible to observe the increase in the roughness with CTAB presence.
Keywords: catalysts support; CTAB surfactant; MgO; oxygen vacancy; sol-gel synthesis